Improvement on the electrochemical performance by morphology control of nanostructured La0.6Sr0.4CoO3-δ-Gd0.1Ce0.9O1.95cathodes for IT-SOFC - Acuña, Leandro Marcelo (2022)
The effect of the particle's shape of Gd0.1Ce0.9O2-d (GDC) nanopowders on the electrochemical performance of La0.6Sr0.4CoO3-δ (LSC)-GDC composite cathodes was experimentally studied by electrochemical impedance spectroscopy (EIS). Composites were made of nanostructured LSC perovskite (average crystallite size D = 30 nm) mixed with nanostructured GDC powder (D = 8 nm) of irregular particle shape or with spherical particles of 200 nm diameter. Symmetrical cells (cathode/electrolyte/cathode) with different weight ratios of LSC:GDC (100: 0, 75 : 25, 50: 50 and 25 : 75 wt%) thick cathodes were fabricated by the screen-printing method and tested by EIS in the temperature range of 500-700 °C under a synthetic air flow of 100 mL min-1. These nanostructured composite materials exhibited excellent performance (area-specific resistance - ASR - values in the range of 0.019-0.032 Ω cm2 for an operating temperature of 700 °C). The best performance was achieved at a weight ratio of 75 : 25 wt% (LSC:GDC) when nanostructured GDC spheres were employed. This enhanced performance can be attributed to GDC morphology along with GDC anionic conduction, which prevent the blocking of LSC electrochemical reaction sites on surface, keeping them active by depleting its surface of adsorbed and reduced oxygen. The limiting processes were determined to take place on the LSC surface. New insight on cobalt's speciation under working-like conditions, determined by in situ X-ray Absorption Spectroscopy (XAS) experiments, suggests that the ease of cobalt atoms for changing their oxidation state is the key feature that rules the electrochemical activity of LSC and an atomistic model that explains it is proposed.